PERBEDAAN MODEL PEMBELAJARAN MIND MAPPING DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IV SD NEGERI 068003 MEDAN TAHUN PEMBELAJARAN2018/2019 - TAMBA, IIN PARIDA (Unversitas Katolik Santo Thomas, 2019)
The Objective of the study is to find out difference of Mind Mapping model with Problem Based Learning model to improve student result of lesson on the saince subject in class IV on thing of SD Negeri 068003 Medan The Year of Study 2018/2019. The population are from the first class until the sixth class consist 372 students. The sample using on the research by sampling purposive consist 58. Students the model using on the research is experimental model one group pre-test post-test design that is by giving a pretest before being given treatment and posttest after being treatment.The model in this study uses experimental conducted in two groups, namely experimental I and experimental II. The instrument used to capture data is a multiple choice test in material changes in form objects.Based on statistical data processing in group I obtained an average result of 66,72 standard deviations 14,21 and a standard error of 2,68 of the total 29 students. For the experimental group II, the average results were 84.31 standard deviations 11,57 and the standard error was 2,18 out of 29 students. By using t-test the writer get the scoring of tscoreis 5,119, if the score calculated with the tscore>ttableis 5,199 > 2,001 (0,05) so that H0 is rejected and the Ha is accepted. It is mean that the are differences between Mind Mapping model and Problem Based Learning model. So that conclusion Problem Based Learning model is significantly affect than Mind Mapping model on the objects toward the result of lesson on the subject in class IV on thing of SD Negeri 068003 Medan, the Year of the Study 2018/2019